The Use of a Cloud-Based Internal Control Information System to Increase Transparency and Accountability at The Law Office of PT. Officium Nobile Indolaw - Selvia Wijaya; F.X Kurniawan Tjakrawala (Green Publisher Indonesia, 2024)
Law firms often face challenges in maintaining transparency and accountability in information management. So with the increasingly complex demands from clients and supervisory institutions, an effective system is needed to manage data and information. The use of a cloud-based internal control information system can be a solution to improve operational efficiency and transparency in law firms. This study aims to explore how the implementation of a cloud-based internal control information system can improve transparency and accountability at PT. Officium Nobile Indolaw. The method used in this study is a qualitative approach with a case study. The results of the study show that the use of a cloud-based internal control information system at PT. Officium Nobile Indolaw aims to improve transparency and accountability in law firm operations. So with cloud-based technology, internal data and processes can be accessed in real-time and more easily monitored by stakeholders, thereby reducing the risk of deviation and strengthening supervision. This system also allows for more efficient and automatic recording, supports faster and more precise decision-making based on accurate data, and increases client confidence in the integrity of the legal process being carried out.